Association of Pre- and Posttreatment Neutrophil–Lymphocyte Ratio With Recurrence and Mortality in Locally Advanced Non-Small Cell Lung Cancer - Sebastian, Nikhil T.; Raj, Rohit; Prasad, Rahul; Barney, Christian; Brownstein, Jeremy; Grecula, John; Haglund, Karl; Xu-Welliver, Meng; Williams, Terence M.; Bazan, Jose G. (Frontiers in Oncology, 2020)
Objectives: Neutrophil-lymphocyte ratio (NLR) has been associated with mortality in non-small cell lung cancer (NSCLC), but its association with recurrence in locally advanced NSCLC (LA-NSCLC), specifically, is less established. We hypothesized pre- and post-treatment NLR would be associated with recurrence and mortality. Methods: We studied the association of pre-treatment NLR (pre-NLR) and post-treatment NLR at 1 (post-NLR1) and 3 months (post-NLR3) with outcomes in patients with LA-NSCLC treated with chemoradiation. Pre-NLR was dichotomized by 5, an a priori cutoff previously shown to be prognostic in LA-NSCLC. Post-NLR1 and post-NLR3 were dichotomized by their medians. Linear and logistic regression were used to correlate thoracic vertebral body dose with post-NLR. Results: We identified 135 patients treated with chemoradiation for LA-NSCLC between 2007 and 2016. Median follow-up for living patients was 61.1 months. On multivariable analysis, pre-NLR ≥ 5 was associated with worse overall survival (HR = 1.82; 95% CI 1.15 – 2.88; p = 0.011), but not with any recurrence, locoregional recurrence, or distant recurrence. Post-NLR1 ≥ 6.3 was not associated with recurrence or survival. Post-NLR3 ≥ 6.6 was associated with worse overall survival (HR = 3.27; 95% CI 2.01– 5.31; p < 0.001), any recurrence (HR = 2.50; 95% CI 1.53 – 4.08; p < 0.001), locoregional recurrence (HR = 2.50; 95% CI 1.40 – 4.46; p = 0.002), and distant recurrence (HR = 2.53; 95% CI 1.49 – 4.30; p < 0.001). Post-NLR3 ≥ 6.6 correlated with thoracic vertebral body volume receiving 5 Gy (p = 0.026), 10 Gy (p = 0.041), and 60 Gy (p = 0.044). Conclusion: Pre-treatment NLR is associated with worse overall survival and post-treatment NLR is associated with worse survival and recurrence. Additionally, post-treatment NLR at 3 months correlates with thoracic vertebral body dose. These findings should be validated independently and prospectively studied.